Prevalence of HIV/AIDS and prediction of future trends in north-west region of India: A six-year ICTC-based study - Vyas Nitya; Hooja Saroj; Sinha Parul; Mathur Anuj; Singhal Anita; Vyas Leela (Wolters Kluwer Medknow Publications, 2009)
Background: The study was conducted to analyze previous six-year prevalence data of HIV infection in the Northwest region of India and predict future trends for a couple of years. Objectives: The study was conducted to aid SACS and NACO to plan and arrange resources for the future scenario. Materials and Methods: All the attendees of ICTC, Jaipur, from January 2002 to December 2007 were included and variables like age, sex, marital status, occupation, place of residence, pattern of risk behavior and HIV serostatus were studied. As per the strategy and policy prescribed by NACO, tests (E/R/S) were performed on the serum samples. Data was collected; compiled and analyzed using standard statistical methods. Future trends of HIV-prevalence in north-west India were anticipated. Results: The overall positivity rates among attendees of ICTC, were found to be 12.2% (386/3161), 11.8% (519/4381), 11.1% (649/5867), 13% (908/6983), 14% (1385/9911) and 17.34% (1756/10133) in the years 2002, 2003, 2004, 2005, 2006 and 2007 respectively. Future trends for the next couple of years depict further increase in prevalence without any plateau. Conclusion: Epidemiological studies should be carried out in various settings to understand the role and complex relations of innumerable behavioral, social and demographic factors, which will help, interrupt and control the transmission of HIV/ AIDS.